Approaches to meaning in music - Almén, Byron; Pearsall, Edward (Musical meaning and interpretation, 2006)
Approaches to Meaning in Music presents a survey of the problems and issues inherent in pursuing meaning and signification in music, and attempts to rectify the conundrums that have plagued philosophers, artists, and theorists since the time of Pythagoras. This collection brings together essays that reflect a variety of diverse perspectives on approaches to musical meaning. Established music theorists and musicologists cover topics including musical aspect and temporality, collage, borrowing and associ
Keywords: Music : Philosophy and aesthetics; Music : Semiotics; Musical analysis